Bis{μ-3-methoxy-N′-[1-(2-oxidophenyl)ethylidene]-benzohydrazidato} bis[pyridinezinc(II)] pyridine solvate - Ali, Hapipah Mohd; Yamin, B.M.; Yusof, M.S.M.; Khamis, N.A. (International Union of Crystallography, 2004)
The title compound, [Zn2(C21H14N 2O3)2(C5H5N) 2]·C5H5N, is dimeric via Zn - O bridging, with an average value for the Zn - O bonds of 2.027 (2) Å. The Zn⋯Zn separation is 3.1546 (5) Å. The molecule has a center of inversion and the coordination geometry of both Zn atoms is square pyramidal. © 2004 International Union of Crystallography Printed in Great Britain - all rights reserved.